Postgraduate design education and sustainability—An investigation into the current state of higher education and the challenges of educating for sustainability - Delaney, Emelia; Liu, Wei (Frontiers in Sustainability, 2023)
Sustainability has remained an important issue within academia and industry, with more recent focus on sustainability education to ensure that future generations are equipped with the knowledge to continue and champion sustainable outcomes. The design and innovation industry has been continuously identified as important by academia, for having high impact on the potential sustainability of products and services during their development. However, little research focuses on the pre-professional education of designers and whether they receive an appropriate education on sustainable issues in relation to their industry. This study investigated these issues within the context of United Kingdom-based postgraduate design courses, to determine the current state of sustainability education as well as the impact of government resources and policies on encouraging sustainability education. Courses were evaluated using Sterling’s model ‘Levels of Response to Sustainability Education’ to understand the current approach to sustainability within design education, including content and pedagogy, offering recommendations for improvement. This study also investigates external factors such as government policies and requirements for accreditation certification to determine the influence on the availability of sustainability education. The outcome of the research is a proposed model for upgrading sustainability education in design courses. Recommendations for future research are also outlined.